2007
DOI: 10.1124/jpet.107.119644
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Intracellular Zinc in Myocardial Ischemia/Reperfusion Is Associated with Preservation of Protein Kinase C Isoforms

Abstract: The recent discovery of zinc signals and their essential role in the redox signaling network implies that zinc homeostasis and the function of zinc-containing proteins are probably altered as a result of oxidative stress, suggesting new targets for pharmacological intervention. We hypothesized that the level of intracellular labile zinc is changed in hearts subjected to ischemia/reperfusion (I/R) and investigated whether the maintenance of myocardial zinc status protected heart functions. Using fluorescent ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 38 publications
(51 reference statements)
5
66
0
1
Order By: Relevance
“…TSQ is a non-acetoxymethyl ester Zn 2 þ indicator. Although it is a very sensitive Zn 2 þ probe (Kd ¼ 10 nM), 10 it does not depend on cleavage of an acetoxymethyl ester group for uptake and fluorescence, so intracellular TSQ leaks out within a few minutes and it is not possible to measure sequential fluorescent changes. 30 The rest of recording detail, please see Supplemental Methods.…”
Section: àKmentioning
confidence: 99%
See 1 more Smart Citation
“…TSQ is a non-acetoxymethyl ester Zn 2 þ indicator. Although it is a very sensitive Zn 2 þ probe (Kd ¼ 10 nM), 10 it does not depend on cleavage of an acetoxymethyl ester group for uptake and fluorescence, so intracellular TSQ leaks out within a few minutes and it is not possible to measure sequential fluorescent changes. 30 The rest of recording detail, please see Supplemental Methods.…”
Section: àKmentioning
confidence: 99%
“…7,8 When a non-acetoxymethyl ester Zn 2 þ indicator, TSQ, is applied to the heart tissues, reperfusion induces a decrease, rather than an increase, in [Zn 2 þ ] i levels. 9,10 When a mixture of Zn 2 þ and the Zn 2 þ ionophore pyrithione is added to the reperfusion solution for 20-30 min, cardioprotection occurs, and two mechanisms have been suggested, namely preservation of protein kinase C (PKC) isoforms and inhibition of mitochondrial metabolism. 9,10 The molecular mechanism for the effect of the [Zn 2 þ ] i increase on cell survival is therefore still debatable.…”
Section: àKmentioning
confidence: 99%
“…Others have also reported a Zn 2+ supplement to be cardioprotective in mice with streptozocin-induced diabetic cardiomyopathy, in rat hearts with ischemia/reperfusion injury or following isoproterenol administration. 62,[90][91][92] Coupled Ca 2+ and Zn 2+ dyshomeostasis. The dyshomeostasis of extra-and intracellular Ca 2+ and Zn 2+ that accompanies ALDOST contributes to a deleterious, but reversible disequilibrium between pro-and antioxidants.…”
Section: Zinc Dyshomeostasis In Aldosteronismmentioning
confidence: 99%
“…Zn 2ϩ has been demonstrated to prevent apoptosis both in vitro and in vivo models (28,41). Recently, it has been reported that the treatment of isolated rat hearts at reperfusion with Zn 2ϩ ionophore pyrithione induces cardioprotection against ischemiareperfusion injury (23). Recent studies from our laboratory have shown that Zn 2ϩ modulates oxidant-induced mPTP opening in isolated rat cardiomyocytes (20) and prevents reperfusion injury by targeting mPTP in cardiac H9c2 cells (4).…”
Section: Discussionmentioning
confidence: 98%